Bir Assur biluntusunun radyografik incelemesi - Tuğrul, Beril
Radiographic Investigation on an Assyrian Artifact; nondestructive analysis of an accreted lump found at Assur: the lump comprises a metal disk with an inscription of Shalmaneser I, and numerous beads